2019
DOI: 10.1111/ppl.12969
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of sterol content and biosynthetic gene expression during flower opening and early fruit development in olive

Abstract: Phytosterols are lipophilic membrane components essential not only for diverse cellular functions but also are biosynthetic precursors of the plant hormone, brassinosteroid (BR). However, the interaction between phytosterol and BR during early fleshy-fruit growth remains largely uncharacterized. In olive, phytosterols are important lipids because they affect oil quality, but phytosterol composition during flowering and early fruit development has not been explored. Here, we first investigated the temporal chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 93 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…The lack of squalene presence was also reported in the olive flowers, where substantial content of sterols was found, while olive oil ( Olea europaea L.) is one of the richest sources of sterols and squalene. [ 17 ] In the last three measurement points, the concentration of squalene did not differ statistically significant within each genotype (86th, 100th, and 114th DAFB). A similar as for sterols, the recorded concentration of squalene in seed oil from mature seeds (114th DAFB) was twofold higher (nearly) than in previous reports.…”
Section: Resultsmentioning
confidence: 98%
“…The lack of squalene presence was also reported in the olive flowers, where substantial content of sterols was found, while olive oil ( Olea europaea L.) is one of the richest sources of sterols and squalene. [ 17 ] In the last three measurement points, the concentration of squalene did not differ statistically significant within each genotype (86th, 100th, and 114th DAFB). A similar as for sterols, the recorded concentration of squalene in seed oil from mature seeds (114th DAFB) was twofold higher (nearly) than in previous reports.…”
Section: Resultsmentioning
confidence: 98%
“…The evolution of sterols directly in the olive pulp [ 50 ] has been less studied, but increases in sterol concentration have indeed been observed in the pulp as ripening progresses. Inês et al [ 51 ] suggested that the increase they observed in sterol biosynthesis in early fruits was because the rates of mitosis and membrane formation were at maximum levels. The complexity of the enzymatic pathways involved in sterol biosynthesis [ 52 , 53 ] and the participation of sterols in the biosynthesis of other compounds [ 37 , 54 ], as well as abiotic stress effects on olives (a less studied factor) [ 53 , 55 ], generate a wide range of variability in sterol concentration throughout ripening.…”
Section: Resultsmentioning
confidence: 99%
“…Olive trees ( Olea europaea L.) of the ‘Picual’ cultivar 20 years old in an orchard under drip irrigation (fertigation with suitable liquid fertilizers) near Badajoz (Spain) were studied. From these trees, flowers were collected at the anthesis stage (0 days post-anthesis, DPA) and fruits were sampled at 7, 14, 21, 28, 35, and 42 DPA, spanning a time from the fruit set to the time of endocarp lignification, and 500 flowers or fruits for each developmental stage during the 2018–2019 growing seasons [ 27 , 62 , 63 ]. Harvested flowers and whole fruits of ‘Picual’ olive were weighed, and the longitudinal and transverse diameters were measured at different developmental stages ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the application of exogenous brassinosteroid (BR) promoted early fruit growth in olive, whereas blocking BR synthesis with brassinazole (Brz) slowed down the fruit growth rate [ 62 ]. Likewise, the data have provided new findings on the role of BRs in modulating the composition and gene expression of sterols and sphingolipids, these being lipophilic membrane components essential for cellular functions during early olive fruit growth [ 62 , 63 ]. This latter study also revealed the upregulation of β -sitosterol biosynthesis by BR at the transcriptional level during early olive fruit growth.…”
Section: Introductionmentioning
confidence: 99%